Upregulation of matrix metalloproteinase triggers transdifferentiation of retinal pigmented epithelial cells in Xenopus laevis: A Link between inflammatory response and regeneration. Issue 9 (26th April 2017) - Naitoh, Hanako; Suganuma, Yukari; Ueda, Yoko; Sato, Takahiko; Hiramuki, Yosuke; Fujisawa‐Sehara, Atsuko; Taketani, Shigeru; Araki, Masasuke
ABSTRACT: In adult Xenopus eyes, when the whole retina is removed, retinal pigmented epithelial (RPE) cells become activated to be retinal stem cells and regenerate the whole retina. In the present study, using a tissue culture model, it was examined whether upregulation of matrix metalloproteinases (Mmps) triggers retinal regeneration. Soon after retinal removal, Xmmp9 and Xmmp18 were strongly upregulated in the tissues of the RPE and the choroid. In the culture, Mmp expression in the RPE cells corresponded with their migration from the choroid. A potent MMP inhibitor, 1, 10‐PNTL, suppressed RPE cell migration, proliferation, and formation of an epithelial structure in vitro. The mechanism involved in upregulation of Mmps was further investigated. After retinal removal, inflammatory cytokine genes, IL‐1β and TNF‐α, were upregulated both in vivo and in vitro. When the inflammation inhibitors dexamethasone or Withaferin A were applied in vitro, RPE cell migration was severely affected, suppressing transdifferentiation. These results demonstrate that Mmps play a pivotal role in retinal regeneration, and suggest that inflammatory cytokines trigger Mmp upregulation, indicating a direct link between the inflammatory reaction and retinal regeneration. © 2017 Wiley Periodicals, Inc. Develop Neurobiol 77: 1086–1100, 2017